A new species of Fibularia from Japanese waters with a redescription of F. japonica and F. ovulum (Echinodermata: Echinoidea: Clypeasteroida) - Tanaka, Hayate; Wakabayashi, Kaori; Fujita, Toshihiko (Zootaxa, 2019)
A new species, Fibularia coffea sp. nov., occurs from shallow waters in Japan. This new species is distinguished from the other species of Fibularia by the following characters: test height is low, oral surface is slightly depressed toward the peristome, number of pores of petal III continues to increase with the test growth, reaching over 30 at TL > 7.5 mm, and black pigments form symmetric pentaradial on aboral surface in living animals. Two further Japanese species, Fibularia japonica and F. ovulum, are redescribed based on the type specimens (F. japonica) and additional specimens (F. ovulum), respectively. A tabular key to the extant species of Fibularia is also provided. A partial fragment of the mitochondrial gene cytochrome oxidase subunit I (COI) of the type specimens of F. coffea sp. nov. and the additional specimen of F. japonica was sequenced for barcoding in future works.